Ultra-fine Crystallization Forging Process of Maraging Steel 18Ni（250） - Xie Bin, Wang Chao, Xu Zhiwei, Liao Xiaolin (Teshugang)
This study optimized the ultrafine grain forging process of 18Ni （250） martensitic aging steel for specific application requirements in deep and low temperature environments， aiming to improve the plasticity and toughness of the material under deep and low temperature conditions. The study analyzed the behavior of materials during hot deformation process and the influence of deformation process on microstructure through hot deformation method， observed the microstructure after hot deformation， and established the constitutive equation and hot working diagram between material rheological stress， deformation temperature， and strain rate. Finally， the optimal heat treatment process area was determined， which is the range of deformation temperature and deformation rate. Research has shown that when the deformation temperature is higher than 1050 ℃ and the deformation is 30 percent， the material exhibits austenite grain recrystallization phenomenon. When the deformation temperature is 1150 ℃， the grain structure tends to refine. Based on the thermal deformation equation and thermal processing diagram with deformation temperature between 850 ℃-1 150 ℃ and strain rate within the range of 0.01 s-1-10 s-1， the ideal thermal processing zone of the material was obtained， which is the deformation temperature range of 1050 ℃-1150 ℃ and the strain rate range of 0.01 s-1-10 s-1.